2005
DOI: 10.1002/mrd.20311
|View full text |Cite
|
Sign up to set email alerts
|

Expression of imprinted genes is aberrant in deceased newborn cloned calves and relatively normal in surviving adult clones

Abstract: Cattle are the species used most frequently for the development of assisted reproductive technologies, such as nuclear transfer. Cattle cloning can be performed by a large number of laboratories around the world, and the efficiency of nuclear transfer in cattle is the highest among 25 all species in which successful cloning has been achieved. However, an understanding of the expression of imprinted genes in this important species is lacking. In the present study, real time reverse-transcription polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 55 publications
(74 reference statements)
4
69
0
3
Order By: Relevance
“…This strongly suggests a correlation between the normality of gene expression and viability of the cloned piglets. Our finding was in accordance with a recent study in which the expression of several imprinted genes were found to be relatively normal in bovine clones that survived to adulthood compared to those that died at/after birth (Yang et al 2005). Interestingly, all the above-mentioned studies, together with ours, reported more variation of gene expression in the cloned group, suggesting the universal random nature of nuclear reprogramming in different species.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This strongly suggests a correlation between the normality of gene expression and viability of the cloned piglets. Our finding was in accordance with a recent study in which the expression of several imprinted genes were found to be relatively normal in bovine clones that survived to adulthood compared to those that died at/after birth (Yang et al 2005). Interestingly, all the above-mentioned studies, together with ours, reported more variation of gene expression in the cloned group, suggesting the universal random nature of nuclear reprogramming in different species.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the expression of all but one gene (ARAF1) in organs of individual deceased clones was found to exceed this threshold and was likely abnormal (Table 2). Similar expression abnormalities were found in DNA methylation in cloned pigs and deceased cloned bovine calves (Archer et al 2003;Li et al, 2004;Yang et al, 2005). The same 2SD comparisons in the surviving clones revealed much less dysregulation (Table 2).…”
Section: Discussionsupporting
confidence: 63%
“…At d 18, the beginning of the implantation window, developmental asynchrony between the embryonic disk and the extraembryonic tissue (EET) was shown to be one reason for arrest at implantation (19). In addition, relatively few differentially expressed genes are detected in cloned fetuses (20,21), and comparison of gene expression in term placentomes collected from pregnancies produced by SNCT, in vitro fertilization, and AI (17) showed that, at later stages of development and at term, placentomes of SCNT-derived pregnancies had an altered transcriptome, regardless of whether pathological morphology was observed (15,17). These studies demonstrated that the abnormal development of the placenta is the major cause of failure of clones to complete pregnancy after implantation.…”
Section: Significancementioning
confidence: 99%
“…The defect in imprinted genes expression was also observed in cloned embryos and even cloned fetuses (Mann et al 2003;Yang et al 2005). In fact, oocytes have few responsibilities to reprogram imprinted genes in sperm genome, for the reason that appropriate epigenetic modifications have already been established in most of imprinted genes during spermiogenesis.…”
Section: Main Barricades Of Reprogramming Somatic Cells By Oocytesmentioning
confidence: 99%
“…There was a contradiction in the question of whether imprinted genes could normally express in live cloned animals because both faithful and unfaithful expression of imprinted genes were reported (Inoue et al 2002;Yang et al 2005;Wei et al 2010;Shen et al 2012;Okae et al 2014). We considered that the abnormalities in the expression of imprinted genes, as well as aberrant DNA methylation in their DMR, are common phenomena in most of cloned embryos.…”
Section: Main Barricades Of Reprogramming Somatic Cells By Oocytesmentioning
confidence: 99%